PEMANFAATAN MEDIA YOU TUBE DALAM MENGEMBANGKAN KEMAMPUAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS VI SD NEGERI TAMANAN 1 - Heru Prayitno, Teguh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Improving students writing skills in elementary schools is one of the main goals of learning Indonesian, but in reality it is not yet optimal. This study aims to improve writing skills in the use of the You Tube video method in Indonesian language learning for elementary school students. With 25 students. The data collection techniques used in this study were: (a) students' Indonesian learning outcomes were collected by giving a writing test at the end of each cycle, (b) data about the teaching and learning process were collected using observation sheets. The collected data were analyzed quantitatively and qualitatively. The results of the analysis show that there is an increase in learning outcomes quantitatively marked by an increase in the average score of students from 66.92 to 78.32 from an ideal score of 100. Qualitatively, there is an increase in the quality of the learning process, namely changes in student attitudes which are marked by: (a) The increased frequency of student attendance, (b) The activeness of students in the teaching and learning process, (c) The more students pay attention to the teacher's explanation, (d) The more students ask questions and answer assignments correctly, (e) The less students ask for guidance and ask to be explained about a concept. Thus, it can be concluded that the application of the serial YouTube video method can improve students' writing skills. And it is suggested to the teacher, to improve learning outcomes in Indonesian, students must be involved in the learning process so that independence is created to solve questions at home about the material that has been studied and the material to be studied next, so that learning using the serial YouTube Vidio method is an alternative method.